Psychological Safety of Educational Environment and Subjective Well-Being of Trainees - Lyusova Oksana Valeryevna (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 11. Estestvennye Nauki, 2015)
The federal government standard defines educational objectives of education and development of such a person who can meet their needs, as well as the needs of society and the state. The standard combines individual, public and state needs. The new standard requires the teaching staff of the institution to create conditions for subjective well-being of trainees. Subjective well-being is regarded as the emotional state of the integral human satisfaction with various aspects of their life and life in general. An important condition for psychological well-being is a specially arranged educational environment in which the student is a significant part of it. Safety is an integral indicator of satisfaction, security, referential educational environment. To study this problem the security educational environment was monitored among schools. The total number of respondents amounted to 810 persons. The main purpose of the monitoring is to provide objective and reliable information about the security role of the educational environment in the formation of subjective well-being of students. The strongest link between security of the educational environment and the subjective wellbeing of students was revealed at schools that implemented pilot programs, innovative projects, in-depth studies of particular subjects. They were identified as protective factors of the educational environment.